Social security strategy as a remedy used for survival (Economic and Political Thought, 2018)
The article shows that in the context of social security, every policy aswell as every strategy will be a periodic concept of simultaneous thinkingand acting in the field of achieving the assumed vision in the area of statesecurity and its future. The above concept is identified as a unity of goalsdistinguished due to their social aspect, nature, scope and timespan of theimplementation of the declared political intentions. It has been shown thatsuch a course of action may be justified by the coercion of support, defenceand protection of safe implementation of the common good. And it can alsobe evaluated as a remedy used for our survival.
Keywords: empire, system, autonomy, policy, strategy, security, development